First record of albatrellus (Russulales, Albatrellaceae) from Thailand - Santhiti Vadthanarat (2018)
© 2017 Magnolia Press. The genus Albatrellus, mostly known from temperate zones in North America, Europe and some Asian countries, is unusual among Russulales in having a poroid hymenophore, as other Albatrellaceae. Albatrellus is reported here for the first time from Thailand, with macro- and micromorphological descriptions and supporting illustrations. Molecular analyses of the internal transcribed spacer (ITS) confirmed that our collection is closely related to Albatrellus subrubescens, but genetic distances suggest that it could be a new species. More collections are needed from Thailand or neighboring countries to firmly establish its taxonomic identity. DNA sequencing of ectomycorrhized root tips, with both ITS (to identify the fungal partner) and psbA-trnH (to identify the plant partner) demonstrated that Pinus kesiya was the ectomycorrhizal host of the Thai collection of Albatrellus.